2022
DOI: 10.3390/ani12121568
|View full text |Cite
|
Sign up to set email alerts
|

Iturin A Rescued STb-R-Induced Pork Skeletal Muscle Growth Restriction through the Hypothalamic-Pituitary-mTORC1 Growth Axis

Abstract: The engineered STb-Rosetta Escherichia coli (STb-R) was designed to investigate the effects of Iturin A on the skeletal muscle growth of weaned piglets. A total of 28 piglets were randomly divided into 4 groups (7 piglets per group): the control group (100 mL PBS), the Iturin A group (100 mL 320 mg/kg body weight (BW) Iturin A), the STb-R group (100 mL 1 × 1010 CFU/mL STb-R), and the Iturin A + STb-R group (100 mL 320 mg/kg BW Iturin A + 1 × 1010 CFU/mL STb-R). Compared with the control, STb-R-reduced body wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Studies have indicated that insulin can bind to insulin receptors, and that phosphorylated insulin receptor substrate 1 ( IRS1 ) regulates protein synthesis in skeletal muscle satellite cells and in the breast tissue of dairy cows by activating signaling pathways such as protein kinase B-target of rapamycin complex 1 ( Akt-TORC1 ; Bolster et al, 2004 ; Yang et al, 2015 ; Xie et al, 2021 ; Ye et al, 2022 ). Our previous study showed that the serum prolactin and insulin contents in lactating pigeons were significantly higher than those in nonbreeding pigeons, and the phosphorylated protein levels of IRS1, Akt, TOR, ribosomal protein S6 kinase 1 ( S6K1 ), ribosomal protein S6 ( S6 ), eukaryotic initiation factor 4E binding protein 1 ( 4EBP1 ), and eukaryotic initiation factor 4E ( eIF4E ) were all upregulated during lactation ( Hu et al, 2016 ).…”
Section: Hormonal Changes and Signaling Pathways Involved In Pigeon C...mentioning
confidence: 99%
“…Studies have indicated that insulin can bind to insulin receptors, and that phosphorylated insulin receptor substrate 1 ( IRS1 ) regulates protein synthesis in skeletal muscle satellite cells and in the breast tissue of dairy cows by activating signaling pathways such as protein kinase B-target of rapamycin complex 1 ( Akt-TORC1 ; Bolster et al, 2004 ; Yang et al, 2015 ; Xie et al, 2021 ; Ye et al, 2022 ). Our previous study showed that the serum prolactin and insulin contents in lactating pigeons were significantly higher than those in nonbreeding pigeons, and the phosphorylated protein levels of IRS1, Akt, TOR, ribosomal protein S6 kinase 1 ( S6K1 ), ribosomal protein S6 ( S6 ), eukaryotic initiation factor 4E binding protein 1 ( 4EBP1 ), and eukaryotic initiation factor 4E ( eIF4E ) were all upregulated during lactation ( Hu et al, 2016 ).…”
Section: Hormonal Changes and Signaling Pathways Involved In Pigeon C...mentioning
confidence: 99%